Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Quick chain rule q

  1. May 4, 2012 #1

    If I have the equation

    [tex] y' = ax - by [/tex]

    where [tex] y = y(t) , x= x(t)[/tex]

    and [tex] y' = \frac{dy}{dt} [/tex]

    then what is

    [tex] \frac {d}{dy} y' = \frac {d}{dy}(ax - by) [/tex]


    I think it would come out to

    [tex] \frac {dy'}{dy} = a \frac {dx}{dt}\frac {dt}{dy} - b [/tex]

    Is that right? In general, is y' a function of y or would the first term on the left be 0?

  2. jcsd
  3. May 5, 2012 #2


    Staff: Mentor

    What you have is good, as far as you went, but you can do more with the expression on the left side of the equation.

    Using the chain rule, we have
    d/dy(y') = d/dy(dy/dt) = d/dt(dy/dt) * dt/dy = y'' * 1/y'
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Similar Discussions: Quick chain rule q
  1. Chain Rule (Replies: 9)

  2. Chain Rule (Replies: 30)

  3. Chain Rule (Replies: 25)

  4. Chain rule. (Replies: 6)

  5. The Chain Rule (Replies: 3)